2008
DOI: 10.1038/ng.125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ten loci associated with height highlights new biological pathways in human growth

Abstract: Height is a classic polygenic trait, reflecting the combined influence of multiple as-yet-undiscovered genetic factors. We carried out a meta-analysis of genome-wide association study data of height from 15,821 individuals at 2.2 million SNPs, and followed up the strongest findings in >10,000 subjects. Ten newly identified and two previously reported loci were strongly associated with variation in height (P values from 4 × 10-7 to 8 × 10-22). Together, these 12 loci account for ~2% of the population variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
393
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(412 citation statements)
references
References 40 publications
16
393
1
2
Order By: Relevance
“…Selection of 54 SNPs used in the study Of the 54 loci influencing human height shown in Supplementary Table 1, 16 were published by Weedon et al, 5 11 by Lettre et al 6 and 27 by Gudbjartsson et al 7 Of the 59 markers reported to be strongly associated with height in these three studies, five were mapped within the same chromosome region. For these loci, we picked up markers with the lowest P-value.…”
Section: Genotyping and Imputationsmentioning
confidence: 99%
“…Selection of 54 SNPs used in the study Of the 54 loci influencing human height shown in Supplementary Table 1, 16 were published by Weedon et al, 5 11 by Lettre et al 6 and 27 by Gudbjartsson et al 7 Of the 59 markers reported to be strongly associated with height in these three studies, five were mapped within the same chromosome region. For these loci, we picked up markers with the lowest P-value.…”
Section: Genotyping and Imputationsmentioning
confidence: 99%
“…BMD is a highly heritable (Pocock et al 1987), complex trait and, similar to human height Lettre et al 2008;Weedon et al 2008), tens or possibly hundreds of loci are believed to influence the variation of BMD, indicating that many loci remain to be identified.…”
mentioning
confidence: 99%
“…Adult height has been most amenable to GWAS for a number of reasons: it is invariably measured or at least self-reported with reasonable accuracy; it is a relatively stable trait; and it shows the highest heritability of all body measures -80% of the population variation in adult height is estimated to be genetic in origin. While the initial adult height GWAS papers were notable for the absence of genes implicated in hormone pathways [1,2], it is very reassuring to see that many of the major genes involved in the GH-IGF1 axis, and other hormonal pathways, were represented among the 180 adult height loci, including PITX1, GH1, GHSR, IGF1R, INSR1, ESR1, CYP19A1 (the aromatase gene), IGF2BP2, and IGF2BP3. These findings confirm the increasing recognition that hormonal modulation of such pathways, even in healthy children, may significantly impact on adult height.…”
mentioning
confidence: 99%